A photocontrolled and self-powered bipedal DNA walking machine for intracellular microRNA imaging. Issue 24 (26th February 2020) - Liu, Chang; Hu, Yanlei; Pan, Qingshan; Yi, Jintao; Zhang, Juan; He, Manman; He, Mengyun; Nie, Cunpeng; Chen, Tingting; Chu, Xia
Abstract : A photocontrolled and self-powered bipedal DNA walking machine for intracellular microRNA imaging has been reported. Abstract : In this work, we report a photocontrolled and self-powered DNA walking machine with bipedal DNAzyme walkers for intracellular microRNA imaging.